Needs Analysis of E-Handout Nuanced Emotional Spiritual Quotient as a Learning Media Supplement on Circulation System Material for Phase F at SMAN 2 Batang Anai - Velia Kharisma; Lufri (Biosel Biology Science and Education, 2024)
People need to keep learning new things because technological advances make it a necessity to remain current. In order for education in Indonesia to remain competitive, updates must be made to the curriculum. Currently, the Merdeka Curriculum is being implemented in Indonesia. The independent curriculum has six dimensions that become a reference, which is called the Pancasila learner profile. One of the six dimensions of the Pancasila student profile is having faith and devotion to God Almighty, which this dimension can be implemented by increasing ESQ. This study aims to determine the needs of ESQ nuanced e-handout learning media in schools. The subject in this research is a biology teacher at SMAN 2 Batang Anai and 40 Phase F students. The type of research is descriptive qualitative, with data retrieval techniques through interviews to biology teachers and filling out questionnaires by students. The results of the study found that teachers at the school had never implemented ESQ in learning. Teachers also argue that an additional learning media is needed that contains ESQ components on the material of the circulatory system. In addition, it was found that students agreed that the development of e-handout learning media with ESQ nuances needs to be done to support understanding and interest in learning, especially the circulatory system material. Therefore, it is obvious that the circulatory system material requires the development of E-Handout with ESQ nuances as a supplement in learning media in high school. Keywords: E-Handout, ESQ, Circulatory System